Text mining and web usage mining for web-based recommender systems - Ashwin Ravi Ittoo. (2008)
This project investigates the application of Text Mining and Web Usage Mining techniques to overcome the drawbacks of traditional recommender systems. Two recommender engines are proposed to deal with the information overload problem. A Text Mining-based recommender engine performs its recommendation functions by employing text mining techniques to learn product information, and a Web Usage Mining-based recommender engine employs patterns on customers' behaviors, which are extracted from Web usage data, to perform the recommendation functions.